Paternal behaviour is associated with high levels of OT in plasma and the presence OTR in the mPOA/BNST in the Mongolian gerbil (Meriones unguiculatus) - Romero-Morales, Luis; García-Saucedo, Brenda; Carmona, Agustín; Cervantes, Fernando A.; Luis, Juana (Frontiers in Ethology, 2024)
The exhibition of paternal behaviour has been associated with high peripheral concentrations of oxytocin (OT) and levels of oxytocin receptors (OTRs) in the paraventricular and supraoptic nuclei of the hypothalamus. The presence of OTRs in the medial preoptic area (mPOA), bed nucleus of the stria terminalis (BNST), medial amygdala (MeA), and olfactory bulb (OB) has not been studied extensively in the paternal context, although these nuclei are essential in the regulation of paternal behaviour. The aim of this study was to determine whether there is an association between paternal response of sexually inexperienced males of the Mongolian gerbils (Meriones unguiculatus) and OT concentrations in plasma, as well as the presence of OTRs in the mPOA, BNST, MeA, and OB. We used sexually inexperienced gerbils: ten paternal (PAT) males and 10 males aggressive with pups (AGG). PAT males and AGG males were subjected to paternal behaviour tests. Then, blood samples were taken to quantify OT concentrations. The brains were dissected for OTR immunohistochemistry analyses. PAT males had significantly higher plasma levels of OT and numbers of cells with OTR immunoreactivity (ir) in the mPOA/BNST. These results indicated an association between paternal behaviour and peripheral concentrations of OT, as well as the presence of OTRs in the mPOA and BNST. This suggests that OT and OTRs could participate in the regulation of paternal behaviour in the Mongolian gerbil.